Corporate collapse : accounting, regulatory, and ethical failure - Clarke, Frank L.; Dean, G. W.; Oliver, K. G.; Clarke, F. (Cambridge, UK ; New York : Cambridge University Press, 2003)
This newly revised edition sheds more light on why accountants often fail to deliver the truth about a company's position or to warn of its impending failure. Well-known examples of corporate collapse from the 1960s to the 1990s and beyond are studied as well as the recent HIH and One.Tel collapses. The volume is essential reading for professional accountants and auditors, company directors and managers, regulators, corporate lawyers and investors.
Includes bibliographical references (p. 365-370) and index.
jeo 08/05/2018
Loans
Keywords: Business ethics; Corporations; Business failures